Psychosocial Status Equality between Familial and Non-Familial Breast Cancer Patients - Suharta Suharta; Ishana Balaputra; Nur Hidayat; Henri Setiawan (STIKep PPNI Jawa Barat, 2022)
Aims: To compare psychosocial status between familial and non-familial breast cancer patients. Methods: This study used a descriptive analytic design with a cross-sectional approach. Population and sampling were taken at Baladika Husada Hospital Jember with a total sampling technique of 90 respondents. The inclusion criteria in this study were a native Jember Regency diagnosed since the end of 2021, histologically documented diagnosis of breast cancer, age range 30-55 years, has a partner (husband), can write and read and is an outpatient or inpatient at a hospital. Baladika Husada Kab. Jember. Patients were excluded if they had stage 4 metastases, were unmarried or divorced, and diagnosed with other chronic diseases. The instrument used was the DASS 21 questionnaire (Depression Anxiety Stress Scale 21) which consisted of 21 self-declaration items. The process of collecting, cleaning, editing and analyzing data was carried out with SPSS version 25.0 using the Mann Withney U Test statistical test. Results: This study involved 90 total respondents consisting of 40 in the category of familial breast cancer and 50 non-familial breast cancer. The p-value >0.05 indicates that there is no significant difference between psychosocial status in familial breast cancer and non-familial breast cancer. Conclusion: Psychosocial status of familial breast cancer patients was not different from that of non-familial. Clinically, these findings indicate the importance of the same model of nursing care between the two patient groups. In the next study, the researcher recommends experimental research that examines various nursing interventions on psychosocial status in both groups.